2019
DOI: 10.1039/c8ra08973f
|View full text |Cite|
|
Sign up to set email alerts
|

Down-regulation of MRPS23 inhibits LPS-induced proliferation and invasionviaregulation of the NF-κB signaling pathway in osteosarcoma cells

Abstract: Mitochondrial ribosomal protein S23 (MRPS23), encoded by a nuclear gene, is a participant in the translation of mitochondrial proteins. Recently, MRPS23 has been reported to be overexpressed in many types of cancers and have a close association with cancer progression. However, the specific roles of MRPS23 in osteosarcoma (OS) remain unknown. In this study, we investigated the expression pattern and biological functions of MRPS23 in OS cells. Our results demonstrated that MRPS23 was up-regulated in OS tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…TMB and MSI are a biomarker for cancer immune checkpoint inhibitors [ 16 , 17 ]. It has been reported that MRPS23 could inhibit NF-κB signaling pathway in OS cell [ 18 ]. Our research also indicated MRPS23 expression level is in relation to the stem cell, infiltration of immune cells, m1A, m5C and m6A in human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…TMB and MSI are a biomarker for cancer immune checkpoint inhibitors [ 16 , 17 ]. It has been reported that MRPS23 could inhibit NF-κB signaling pathway in OS cell [ 18 ]. Our research also indicated MRPS23 expression level is in relation to the stem cell, infiltration of immune cells, m1A, m5C and m6A in human cancer.…”
Section: Discussionmentioning
confidence: 99%